Enhanced release of IgE-dependent early phase mediators from nasal polyp tissue - Perez-Novo Claudina; Gevaert Philippe; Affleck Karen; Holtappels Gabriele; Patou Joke; Van Cauwenberge Paul; Bachert Claus (BMC, 2009)
Abstract Background The mast cell is a crucial effector cell in allergic rhinitis and other inflammatory diseases. During the acute allergic reaction preformed mediators such as histamine, but also de novo produced mediators such as leukotrienes (LTC4/D4/E4) and prostaglandins (PGD2) are released. Mast cells represent targets for therapeutic intervention, and thus a human ex-vivo model to stimulate mast cells taken from mucosal sites would be instrumental for drug intervention studies. We have aimed to activate mast cells within ex-vivo human nasal tissue by IgE/anti-IgE specific (ε chain specific) stimulations and in this respect to test the usability of nasal polyps versus inferior turbinates Methods Biopsy samples were collected from patients with nasal polyps and inferior turbinates from patients who underwent sinus or septal surgery. Tissue fragments were primed with IgE 1 μg/ml for 60 minutes and then stimulated for 30 minutes with tissue culture medium (negative control), anti-IgE 10 μg/ml, anti-IgE 30 μg/ml and ionomycin 10 μM (positive control). Histamine, leukotrienes and PGD2 were measured in supernatants. To help provide an understanding of the extent of the response, the number of tryptase and FcεRIα positive cells was evaluated by means of immunohistochemistry and the FcεRIα-chain was measured by means of quantitative PCR in the nasal polyp and inferior turbinate tissues. Finally, the correlation between IgE concentrations in the nasal tissue and the release of mediators was analysed. Results Stimulations with anti-IgE on IgE-primed nasal tissue fragments lead to a concentration-dependent release of histamine, leukotrienes and PGD2. The release of these early phase mediators was significantly higher in nasal polyps compared to inferior turbinates, although tryptase, FcεRIα positive cells and FcεRIα-chain transcripts were equally present in both groups. No correlation was found between baseline concentrations of IgE, and the release of histamine, LTC4/LTD4/LTE4 and PGD2 after stimulation. Conclusion This human nasal challenge model mimics the allergic early phase reaction. The release of histamine, cys-leukotrienes and PGD2 was significantly higher in nasal polyps versus inferior turbinates, however, this observation could not be explained by differences in mast cell or FcεRI+ cell numbers.